Cost-benefit analysis in demand response with penalty and grid management using blockchain - Manikandan Ramasamy; Thenmalar Kaliannan; Saravanakumar Ramasamy (AIP Advances)
In a power system network, balancing energy demand is a difficult issue. In this case, a microgrid is a grid-connected system that combines wind and solar power. Demand response and renewables have a significant impact on how well electricity distribution networks operate. Here, three scenarios are examined: microgrid energy management, consumer penalty, and grid management with blockchain (BC) technology advancements. Renewable energy sources, such as solar and wind units, with a curtailed incentive-based demand response scheme, are discussed in this paper along with economic dispatch. This study aims to optimize utility benefits while minimizing transaction and conventional power costs. Two distinct optimization methods such as the gray wolf optimization algorithm and particle swarm optimization are employed to solve the optimization model. Three units with three customer test systems are proposed to implement this work. Customers are given penalties when they fail to use renewable energy. BC technology is offered as a way to safeguard energy transactions between the grid and microgrid. Ultimately, outcomes are acquired and compared using optimization methods for test system results. A 24-h scheduling interval is used to produce optimization results.